Pain assessment and management: An audit of practice at a tertiary hospital - Prempeh, Nana Agya Boakye Atonsah (Department of Anaesthesia and Perioperative Medicine, 2020)
Background: Despite advances in techniques and analgesics for pain management, pain remains a major health problem. Regular assessment and reassessment of pain using guidelines with measurable goals is essential for effective pain management in acute hospital settings. Unfortunately, no such guidelines exist in South Africa. To implement appropriate precepts for the South African context, current practice must be understood. Aim: To evaluate pain assessment and management of patients in two surgical wards at Groote Schuur Hospital. Setting: Groote Schuur Hospital is a government-funded tertiary academic institution within the Western Cape Province of South Africa. The patients at this hospital are generally from the low-income strata and live in resource-poor communities. Methods: A cross-sectional, retrospective medical record audit was conducted. The folders of all 215 patients admitted to a specific orthopaedic trauma and urogynaecological ward at Groote Schuur Hospital in June 2015 were targeted for review. Medical folders not available or with missing notes were excluded. Variables evaluated included the number of pain assessments recorded, pain assessor, assessment tool and management plan. Results: 168 folders were available for review. Nearly half of the patients had no documented pain assessment. When pain assessment was conducted, the verbal rating scale was the predominant tool used, and assessments were mostly conducted by the ward doctor. Pain interventions appeared to be primarily based on the professional knowledge and experience of the practitioner and were not evidence-based. Conclusion: Pain assessment and management was a problem in the two wards reviewed, which is similar to the findings of studies referenced in this text. Health professionals need to be empowered to manage pain adequately. An assessment tool, which integrates the biopsychosocial factors that influence the pain experience, should be routinely employed by a multidisciplinary team to facilitate goal-directed therapy.